Digitalization and Automatization on the Performance of Employees of the Karanganyar Environmental Service through Job Satisfaction - Rahayu Pancaningsih; Agus Suyatno; Esti Dwi Rahmawati (International Journal of Management, Accounting & Finance (KBIJMAF), 2025)
This study aims to examine the effect of digitalization and automation on employee performance, with job satisfaction as a mediating variable. The background of this research is based on the dynamics of modern organizations that are required to continuously adapt to technological developments, particularly in the era of digital transformation. The implementation of digital technology and automation systems has become a key strategy for improving operational efficiency, accelerating work processes, and optimizing workforce productivity. However, this transformation also poses new challenges, particularly regarding how technology impacts employee job satisfaction and overall performance. This study employed a quantitative approach with a survey method. A questionnaire using a 4-point Likert scale was distributed to 65 employees of the Karanganyar Regency Environmental Agency. Data collection was conducted directly, and data analysis was conducted using Structural Equation Modeling-Partial Least Squares (SEM-PLS) to examine the relationships between variables and the mediating role of job satisfaction. The results indicate that digitalization and automation have a positive and significant impact on employee performance. Furthermore, job satisfaction was also shown to play a significant mediating role in strengthening the influence of digitalization and automation on performance. These findings demonstrate that the success of technology implementation in the workplace is not solely determined by technical aspects, but also depends heavily on how the technology improves employee well-being and job satisfaction. Therefore, organizations need to consider employee psychological aspects at every stage of their digital transformation. This research provides theoretical and practical contributions to understanding the role of digitalization and automation in improving employee performance through a job satisfaction-oriented approach.